EVALUATING THE VISITOR EXPERIENCE AT DNCC WONDERLAND: AN EMPIRICAL INVESTIGATION OF KEY ATTRIBUTES - Habib, Md. Wahidul; Mahmud, Aditi Sonia Mansur (Centre For Tourism Planning and Development, 2020)
DNCC Wonderland is one of the leading amusement park situated in Shyamoli, Dhaka. It was established in 1985 under the name of Shishu Mela. This research evaluates the development of this amusement park. The goal of this research is to identify key variables that can be used to evaluate DNCC Wonderland from the visitors? perspective. Four hundred and twenty-six respondents were selected by convenience sampling procedure for the study. A multivariate analysis technique like ?Exploratory Factor Analysis? and ?Confirmatory Factor Analysis? was used to identify the factors. The results of the study show that time pass, security, and safety have emerged important factors for selecting DNCC Wonderland.